With All Due Respect, Sir: Canadian Forces’ Chaplains: Defining Competencies for Providing Ethical Advice to the Chain of Command - Parker, Neil (Université Saint-Paul / Saint Paul University, 2014)
The role of the Chaplain Branch of the Canadian Armed Forces (CAF) is to “advise commanders on spiritual, religious, moral and ethical issues affecting Canadian Forces personnel and their families during operations and in static situations.” This paper explores the nature of one particular facet of this mandate, ethical expertise, in the complex ethical environment of the contemporary military organization. The study lists criteria necessary to evaluate and substantiate ethical expertise (knowledge, skills, abilities), and relates these to the chaplain’s dual accountability to her or his faith tradition as well as to the military. The study examines the traditional role of the chaplain, the expectations (implicit and explicit) that attach to that role; the role conflict of being a faith group representative and at the same time being embedded in the military organization; the role of faith-based ethics in a pluralistic and public arena; an examination of the criteria that would define “effective” provision of ethical advice; and a discussion of the implications for equipping new and existing chaplains to fulfill this role. The secular and pluralist military environment, dual accountability, and traditional role expectations, all increase the complexity of the task of advising the commander. Moreover, giving ethical advice is on a different plane of moral complexity than that of being personally ethical, and requires a level of expertise that is here defined by specific attributes.
Keywords: Chaplain Aumonier; Canadian Forces; moral development; ethical advising; professional capability